Islamic liberation theology resisting the Empire - Dabashi, Hamid 1951- (Routledge, Taylor & Francis Group, 2008)
This book is a radical piece of counter-intuitive thinking on the clash of civilizations theory and global politics. The author argues that after 9/11 we have not seen a new phase in a long running confrontation between Islam and the West, but that such cataegories have collapsed. The West is no longer a unified actor and Islam is ideologically exhausted in its confontation with colonialism. Rather we are seeing the emergence of the US as a lone superpower, and a confrontation between a form of imperial globalized capital and a new Islamic theodicy.
Keywords: Internationalisatie; Islam; Politieke aspecten; Globalisierung; Politik; Religion; Religious awakening -- Islam; Islam and world politics; Islamic renewal -- Islamic countries; Globalization -- Religious aspects -- Islam; Islam -- 21st century; Theologie; Liberalisierung; Islamic countries -- Politics and government; Westliche Welt